Effectiveness of an advanced hemostatic pad combined with harmonic scalpel in thyroid surgery. A prospective study. (April 2016) - Ruggiero, Roberto; Docimo, Ludovico; Tolone, Salvatore; De Palma, Maurizio; Musella, Mario; Pezzolla, Angela; Gubitosi, Adelmo; Parmeggiani, Domenico; Pirozzi, Raffaele; Gili, Simona; Parisi, Simona; D'Alessandro, Antonio; et al.
Abstract: Introduction: Hemostasis during thyroidectomy is essential; however the most efficient and cost-effective way to achieve this is unclear. The aim of this study was to evaluate the outcome of total thyroidectomy (TT) performed with the combination of harmonic scalpel (HS) and an advanced hemostatic pad (Hemopatch). Methods: Patient undergone TT were divided into two groups: HS + hemopatch and HS + traditional hemostasis groups. The primary endpoint was 24-h drain output and blood-loss requiring reintervention. Secondary endpoints included surgery duration, postsurgical complications and hypocalcemia rates. Results: Between September 2014 and March 2015, 60 patients were enrolled (30 to Hs + Hemopatch, 30 to Hs and standard hemostasis); 71.4% female; mean age 48.5 years. The 24-h drain output was lower in the HS + hemopatch group compared with standard TT. HS and hemopatch also had a shorter mean surgery time (p < 0.0001) vs standard TT. Conclusion: combination of hemopatch plus HS is effective and safe for TT with a complementary hemostatic approach.